Phenotypic spectrum of CHARGE syndrome in fetuses with CHD7 truncating mutations correlates with expression during human development. Issue 3 (16th September 2005) - Sanlaville, D; Etchevers, H C; Gonzales, M; Martinovic, J; Clément-Ziza, M; Delezoide, A-L; Aubry, M-C; Pelet, A; Chemouny, S; Cruaud, C; Audollent, S; Esculpavit, C; et al.
Abstract : Background: The acronym CHARGE refers to a non-random cluster of malformations including coloboma, heart malformation, choanal atresia, retardation of growth and/or development, genital anomalies, and ear anomalies. This set of multiple congenital anomalies is frequent, despite rare patients with normal intelligence, and prognosis remains poor. Recently, CHD7 gene mutations have been identified in CHARGE patients; however, the function of CHD7 during development remains unknown. Methods: We studied a series of 10 antenatal cases in whom the diagnosis of CHARGE syndrome was suspected, considering that a careful pathological description would shed light on the CHD7 function during development. CHD7 sequence analysis and in situ hybridisation were employed. Results: The diagnosis of CHARGE syndrome was confirmed in all 10 fetuses by the identification of a CHD7 heterozygous truncating mutation. Interestingly, arhinencephaly and semi-circular canal agenesis were two constant features which are not included in formal diagnostic criteria so far. In situ hybridisation analysis of the CHD7 gene during early human development emphasised the role of CHD7 in the development of the central nervous system, internal ear, and neural crest of pharyngeal arches, and more generally showed a good correlation between specific CHD7 expression pattern and the developmental anomalies observed in CHARGE syndrome. Conclusions: These results allowed us to further refine the phenotypic spectrum of developmental anomalies resulting from CHD7 dysfunction.